2017
DOI: 10.1155/2017/2837685
|View full text |Cite
|
Sign up to set email alerts
|

Does Dopamine Depletion Trigger a Spreader Lexical-Semantic Activation in Parkinson’s Disease? Evidence from a Study Based on Word Fluency Tasks

Abstract: It has been hypothesised that, in Parkinson's disease (PD), dopamine might modulate spreading activation of lexical-semantic representations. We aimed to investigate this hypothesis in individuals with PD without dementia by assessing word frequency and typicality in verbal fluency tasks. We predicted that the average values of both of these parameters would be lower in PD patients with respect to healthy controls (HC). We administered letter-cued and category-cued fluency tasks to early PD patients in two exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In this regard, the analysis of the dynamic change of lexical frequency instead of the overall word frequency of all responses (which did not differ between groups or medication conditions in our study) might be a more sensitive measure of semantic activation underlying word search and retrieval. Other studies, which included lexical frequency in their analysis of semantic or phonemic VF, also reported no difference between PD groups and controls regarding the overall word frequency in semantic and phonemic VF (Herrera et al, 2012 ; Zabberoni et al, 2017 ; Wagner et al, 2020 ). One study, however, observed an increased mean word frequency of verbs produced by the PD group, which was not attributed to altered semantic activation but rather disrupted coupling between motor abilities and cognition (Herrera et al, 2012 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In this regard, the analysis of the dynamic change of lexical frequency instead of the overall word frequency of all responses (which did not differ between groups or medication conditions in our study) might be a more sensitive measure of semantic activation underlying word search and retrieval. Other studies, which included lexical frequency in their analysis of semantic or phonemic VF, also reported no difference between PD groups and controls regarding the overall word frequency in semantic and phonemic VF (Herrera et al, 2012 ; Zabberoni et al, 2017 ; Wagner et al, 2020 ). One study, however, observed an increased mean word frequency of verbs produced by the PD group, which was not attributed to altered semantic activation but rather disrupted coupling between motor abilities and cognition (Herrera et al, 2012 ).…”
Section: Discussionmentioning
confidence: 97%
“…An increase of lexical frequency in this context is rather reminiscent of lexical simplification of language due to the substitution of single words by highly frequent alternatives as observed in conditions with speech impairment (e.g., Bird et al, 2000 ; Cuetos et al, 2002 ; Boukrina et al, 2015 ; Faroqi-Shah and Milman, 2018 ; Tiedt et al, 2021 ). However, another study, which analyzed the dynamic change of lexical frequency during VF by means of the median split analysis in a PD group (ON and OFF medication) and healthy controls did not yield significant differences between either medication conditions or participant groups with respect to the change (i.e., decrease) of word frequency during VF tasks (Zabberoni et al, 2017 ). A possible explanation could be a longer duration of each individual VF task in our study (2 min as compared to one).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Late-stage PD patients in an off-medication condition were able to outperform healthy controls at verbal fluency when producing verbs but were otherwise poorer than control and their own on-medication performance on all other measures of verbal fluency (phonemic and categorical (Herrera et al, 2012)). By comparison, early PD patients have demonstrated comparable verbal fluency performance to healthy controls both on- and off-medication, with little difference between phonemic or categorical fluency (Zabberoni et al, 2017).…”
Section: Discussionmentioning
confidence: 99%